Production of hydrogen-containing gas by vapor conversion of ethanol - M. S. Yakimova; V. F. Tretyakov; N. A. Frantsuzova; L. O. Yarygina (Тонкие химические технологии, 2010)
Development of the hydrogen power technologies demands new simple and effective methods for hydrogen production from renewable sources. Bio-ethanol produced by biomass fermentation can be used as a raw material for hydrogen production. In this work we studied the conversion of ethanol to hydrogen containing gas on Cu/CeO2 systems. We showed that optimal copper concentrations for these catalysts are within the range of 5-10%. This enables to achieve the reasonable yield of hydrogen at high ethanol conversion values. The main advantage of the proposed catalytic systems is the very low yield of carbon monoxide, which is necessary for further use of the obtained gas in fuel cells.